Hybridization of an Aβ-specific antibody fragment with aminopyrazole-based β-sheet ligands displays striking enhancement of target affinity1. Issue 10 (14th March 2015) - Hellmert, Marco; Müller-Schiffmann, Andreas; Peters, Max Sena; Korth, Carsten; Schrader, Thomas
<x xml:space="preserve">Abstract</x> A His-tagged antibody is combined with an NTA-β-sheet breaker and displays a striking increase in Aβ affinity.